Dipolar Bose-Einstein condensates with large scattering length - Young-S, Luis E. [UNESP]; Adhikari, S. K. [UNESP]; Muruganandam, P. [UNESP] (American Physical Society (APS), 2012)
A uniform dilute Bose gas of known density has a universal behavior as the atomic scattering length tends to infinity at unitarity while most of its properties are determined by a universal parameter ξ relating the energies of the noninteracting and unitary gases. The usual mean-field equation is not valid in this limit, and beyond mean-field corrections become important. We use a dynamical model including such corrections to investigate a trapped disk-shaped dipolar Bose-Einstein condensate (BEC) and a dipolar BEC vortex for large scattering length. We study the sensitivity of our results on the parameter ξ and discuss the possibility of extracting the value of this parameter from experimental observables. © 2012 American Physical Society.